Metal-Free Graphitic Carbon Nitride Photocatalyst Goes Into Two-Dimensional Time - Zhao, Gang; Yang, Hongcen; Liu, Mengqi; Xu, Xijin (Frontiers in Chemistry, 2018)
Graphitic carbon nitride (g-C3N4), as a metal-free and visible-light-responsive photocatalyst, is always a research hotspot in the field of solar energy conversion (hydrogen-production of water splitting). Here, the critical review summarizes a panorama of the latest progress related to the design and syntheses of two-dimensional (2D) g-C3N4 and g-C3N4-based nanocomposites, including (1) the modifications of organic carbon nitrogen precursors, such as heat treatment, metal or metal-free atoms doping, and the modifications with organic functional groups, (2) the influence factors on the formation of two-dimensional g-C3N4 process, including the calcination temperature and protective atmosphere, etc, (3) newly 2D g-C3N4 nanosheets prepared from pristine raw material and bulk g-C3N4, and the combination of 2D g-C3N4 with other 2D semiconductors or metal atoms as cocatalysts, (4) the structures and characteristics of each classification of 2D g-C3N4 systems, together with their optical absorptions band structures and interfacial charge transfers. Apart from those, the first-principles density functional theory (DFT) calculations of the g-C3N4 systems will be summarized, and then to provide insightful outlooks on the development of 2D g-C3N4 photocatalysts. This comprehensive review will end up with a summary, and some exciting perspectives on the challenges and future directions of 2D g-C3N4 photocatalyst are discussed and highlighted in this research platform. It is expected that this review can excite a new research way to facilitate the next generation of 2D g-C3N4 photocatalysts with well performances.